2019
DOI: 10.33594/000000155
|View full text |Cite
|
Sign up to set email alerts
|

FTY720P Upregulates the Na+/K+ ATPase in HepG2 Cells by Activating S1PR3 and Inducing PGE2 Release

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Several reports have documented that PI3K, which is one of the wortmannin targets, regulates crosstalk between V-ATPase and F-actin in osteoclasts ( 55 ) or that PI3K has been involved in “regulated V-ATPase assembly” in dendritic cells ( 56 ). It has been shown in some studies that the S1PR2/S1PR3 axis regulated Na + /K + ATPase in the hepatocellular carcinoma cell line ( 57 , 58 ), while others have indicated that Na + /K + ATPase might serve as an alternative for V-ATPase in astrocytes ( 59 ). Considering V-ATPase inhibitor (Baf A1) enhanced NET formation in parallel with depletion of lysosomal proteins ( Figure 8 ) while S1PR2 ligation restored these proteins, we assumed S1PR2/3 signaling is involved in the reciprocal regulation of V-ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have documented that PI3K, which is one of the wortmannin targets, regulates crosstalk between V-ATPase and F-actin in osteoclasts ( 55 ) or that PI3K has been involved in “regulated V-ATPase assembly” in dendritic cells ( 56 ). It has been shown in some studies that the S1PR2/S1PR3 axis regulated Na + /K + ATPase in the hepatocellular carcinoma cell line ( 57 , 58 ), while others have indicated that Na + /K + ATPase might serve as an alternative for V-ATPase in astrocytes ( 59 ). Considering V-ATPase inhibitor (Baf A1) enhanced NET formation in parallel with depletion of lysosomal proteins ( Figure 8 ) while S1PR2 ligation restored these proteins, we assumed S1PR2/3 signaling is involved in the reciprocal regulation of V-ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…However, the pharmacodynamic reduction in heart rate can be circumvented by implementation of drug titration for the first 4-5 days of treatment, as demonstrated in most patients being treated with siponimod [5] and in the ozanimod trials [11,12]. Fingolimod has also been shown to induce the inflammatory mediator cyclooxygenase 2 (COX2) in rat astrocyte cell cultures [41], and increase COX2 expression in mice and human HepG2 cell cultures via S1PR 3 [42,43], suggesting that activity at this receptor may contribute to inflammatory processes. However, unlike S1P, in vitro studies have shown that fingolimod may be a partial agonist of S1PR 3 compared with S1P, and possibly have antagonistic properties under certain conditions [44][45][46], so the biological significance of this observation is unclear.…”
Section: Figmentioning
confidence: 99%
“…We identified PGE 2 as a regenerative factor both in 2D and 3D human tissue cultures and as a mediator of the IL1β-induced response. Previous work implicating PGE 2 in this pathway has not investigated its effect on primary human hepatocytes ( 55 57 ). In the future, treatment with PGE 2 might be considered for use as a preconditioning agent for liver transplants, or PGE 2 -releasing depots could be incorporated into engineered grafts in order to promote the expansion of engrafted hepatocytes in vivo, even in the absence of an injury stimulus.…”
Section: Discussionmentioning
confidence: 99%